2013
DOI: 10.1063/1.4831963
|View full text |Cite
|
Sign up to set email alerts
|

Di-interstitial defect in silicon revisited

Abstract: Complementary infrared and transmission electron microscopy studies of the effect of high temperature-high pressure treatments on oxygen-related defects in irradiated silicon Hydrogen-defect complexes formed by neutron irradiation of hydrogenated silicon observed by optical absorption measurement Infrared spectroscopy was used to study the defect spectrum of Cz-Si samples following fast neutron irradiation. We mainly focus on the band at 533 cm À1 , which disappears from the spectra at $170 C, exhibiting simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…It should be mentioned, however, that the assignment is tentative. Further, the defect, which gives rise to the 533 cm −1 line, anneals out in the temperature range 170–200 °C , and this result is not consistent with the predicted high mobility of I 2 .…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…It should be mentioned, however, that the assignment is tentative. Further, the defect, which gives rise to the 533 cm −1 line, anneals out in the temperature range 170–200 °C , and this result is not consistent with the predicted high mobility of I 2 .…”
Section: Introductionsupporting
confidence: 57%
“… are metastable and have a magnetic field tensor at variance with that of the Si‐P6 ESR signal. Londos et al have recently assigned an absorption band at 533 cm −1 , which they have observed in the infrared absorption spectra of the neutron‐irradiated Si, to a local vibrational mode due to the I 2 defect. It should be mentioned, however, that the assignment is tentative.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Londos et al (2013) have studied CZ-Si after fast neutron irradiation, and have in particular focused on the 533 cm À1 band which in many respects resemble the P6 defect. The band is observed to begin to decay at $170°C with an activation energy of 0.88 AE 0.03 eV.…”
Section: The Di-interstitialmentioning
confidence: 99%